2016
DOI: 10.18172/cig.2927
|View full text |Cite
|
Sign up to set email alerts
|

Long-term drought variability and trends in Barcelona (1787-2014)

Abstract: ABSTRACT. Long-term drought variability and trends were assessed inBarcelona at annual and seasonal scale for the period 1787-2014 and sub-periods 1851-2014, 1901-2014 and 1951-2014 , although the SPEI was indicating the trend towards drier conditions for the whole period 1851-2014, 1901-2014 y 1951-2014

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Catalonian droughts' knowledge is most of all based on drought events' variability studies, either historically avoiding any future SPI (standardized precipitation index) and SPEI (standardized precipitation-evaporation index) indicators projection [13], or assessing climate change effects without considering the representative concentration pathways (RCPs) presented in the Intergovernmental Panel on Climate Change (IPCC) fifth assessment report [14].…”
Section: Introductionmentioning
confidence: 99%
“…Catalonian droughts' knowledge is most of all based on drought events' variability studies, either historically avoiding any future SPI (standardized precipitation index) and SPEI (standardized precipitation-evaporation index) indicators projection [13], or assessing climate change effects without considering the representative concentration pathways (RCPs) presented in the Intergovernmental Panel on Climate Change (IPCC) fifth assessment report [14].…”
Section: Introductionmentioning
confidence: 99%
“…Vicente-Serrano (2013) identified several regions in Spain showing an increase in the severity of droughts (particularly Southwestern Spain, Catalonia and the Central Ebro basin) (see also Coll et al, 2016;Gouveia et al, 2016). An increase in the duration of dry spells in the Central Ebro Valley was detected by López-Moreno et al (2010) in winter, spring and summer, and González-Hidalgo et al (2011) recorded a large decline in the late winter and early spring precipitation (February-March).…”
Section: Discussionmentioning
confidence: 99%
“…In continental Spain, Vicente-Serrano et al (2014b) showed a general decrease in relative humidity from the decade of 1960, mainly associated with a general decrease in the moisture transport to the Iberian Peninsula as well as a certain precipitation decrease. Similarly, Espadafor et al (2011) and Vicente-Serrano et al (2014b) showed that the strong increase in ET o in the last decades is associated with the relative humidity decrease due to air temperature rise, which caused more severe drought events (Coll et al, 2016;Lorenzo-Lacruz and Morán-Tejeda, 2016; Peña- Gallardo et al, 2016). In the Canary Islands, no precipitation changes have been identified during the analysed period (Sánchez-Benitez et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This uneven distribution of meteorological observatories constrains the high interest to know the evolution of atmospheric processes in this region, where climate variability is strongly controlled by changes in the Hadley circulation (Hansen et al, 2005) that affect the position and intensity of the subtropical anticyclone belt. Knowing the evolution of AED and its main drivers in this region is highly relevant given the general climate aridity of the region and the low availability of water resources (Custodio and Cabrera, 2002). In this work we analyse the recent evolution and meteorological drivers of the AED in the Canary Islands.…”
Section: Introductionmentioning
confidence: 99%